How to Become Indispensable - Anna Jobér (Universidade de Lisboa, 2020)
During the 00s, the hiring of private tutors became a common and profitable practice in Sweden. The aim of this article is to illuminate educational policy space and policy processes through the case of private tuition practice in Sweden. The article offers a critical analysis and illuminates discourses that build up a private tuition network with shared ways of acting and talking, contributing to policy in the making. The data foremost consist of newspaper articles, interviews and websites and were analysed with network ethnography and the What's the problem represented to be? approach. The analysis shows a network involving human and non-human actors highlighting an education that is in a crisis - a message underpinned with assumptions that suit the network's needs, thus becoming indispensable for actions. The network occupies space, and through problematisation, determine what is considered to be significant in education and society, in Sweden as well as elsewhere.